Kegiatan Pemeriksaan Kulit Wajah dalam Rangka Deteksi Dini Jerawat pada Populasi Usia Produktif - Donatila Mano S; Yohanes Firmansyah; Farell Christian Gunaidi; Shelma Tria Amanda; Arni Ismi Fadhila (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Acne vulgaris, commonly known as acne, is a dermatological condition that is common among adolescents, affecting approximately 95% of this population. This multifactorial disease consists of genetic, hormonal, microbial, and environmental factors. The main harmful processes are more sebum production, hyperkeratinization, and colonisation with Propionibacterium acnes, which makes porphyrins that make the skin swell. This activity uses the PDCA (Plan-Do-Check-Action) methodology, which involves the facial skin analysis of 170 participants. According to the examination results, the average porphyrin content on the participants' facial skin was 63%. Early detection through comprehensive skin assessment and educational interventions is critical to preventing chronic and recurrent episodes, thereby improving physical and psychological well-being.